If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 11 = 3 + 21 Reorder the terms: 11 + 3x = 3 + 21 Combine like terms: 3 + 21 = 24 11 + 3x = 24 Solving 11 + 3x = 24 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + 3x = 24 + -11 Combine like terms: 11 + -11 = 0 0 + 3x = 24 + -11 3x = 24 + -11 Combine like terms: 24 + -11 = 13 3x = 13 Divide each side by '3'. x = 4.333333333 Simplifying x = 4.333333333
| x-15/16=-1.0364 | | 4a-2b=10 | | w+63=8w | | 43+5y-6=16y-11-3y | | 2(3r-7)+4(3r+2)=(5r+9)+3 | | 3x+11=3x-21 | | 690x-(18000+60x+x^2)=p | | 17+8z=17 | | 7.9x-3.4=4.5 | | 6/9x=42 | | 130/0.25 | | 3.6p-5=13.9 | | 3.6p-5=13 | | (360-230)/0.25 | | t/-710 | | -9=.45m | | 9360-230)/.25 | | 5x+19=x-7 | | 26+16x=15x | | 54=16v | | X+2=-10+4x | | 6(0.5+1)= | | (8x/5)/(1-3/10) | | 9546x-3440=86(111x-40) | | 6x+7=-5+7x | | 8c-2d= | | 7x+2=2-2x | | 4(10x+1)=40x-5 | | 13x+2(2x+1)=10 | | h/8-13=12 | | 0.002+15=2n | | 29-7c=-4(9c+5) |